How Do We Do This? Distance Learning in Physical Education — Part 2. Issue 4 (4th May 2021) - Killian, Chad M.; Daum, David N.; Goad, Tyler; Brown, Ryan; Lehman, Sean
Abstract: Distance learning is something many physical educators never thought they would have to do, given the practical and philosophical contradictions inherent in teaching and learning movement-based content through a computer. Yet, the COVID-19 pandemic has forced most physical education teachers to transition to distance learning modalities. Questions abound regarding the maintenance of quality physical education within the generally unfamiliar online teaching and learning environment. Therefore, the purpose of this three-part series of articles is to address common questions from teachers and students about providing engaging, meaningful online physical education during the pandemic and beyond. The first article focuses on questions related to meeting the needs of low-income students, strategies for at-home equipment, teaching online elementary physical education, engaging parents, and online relationship building. This article answers questions about determining student workload, developing content beyond personal fitness, designing engaging synchronous and asynchronous lessons, assessing meaningfully online, and accommodating learning for all students. Finally, the third article provides discussion about the broader impact of the COVID-19 pandemic on teaching and learning in physical education and offers strategies for transitioning back to face-to-face learning. The ideas and strategies provided throughout this series are meant to be general guidelines for physical education teachers to consider and adjust to fit their own unique community contexts.